Association of COVID-19 pandemic-related concern and health routine changes with functioning among individuals with systemic lupus erythematosus. Issue 1 (17th February 2022) - Plantinga, Laura C; Hoge, Courtney; Dunlop-Thomas, Charmayne; Pearce, Brad D; Lim, S Sam; Drenkard, Cristina; Bowling, C Barrett
Abstract : Objective: To examine whether pandemic-related issues were associated with physical functioning, community mobility and cognition among individuals with SLE. Methods: Participants were recruited (6 October 2020–11 November 2021) for this cross-sectional study from a population-based cohort of individuals with validated SLE in metropolitan Atlanta, as part of an ongoing ancillary study. Pandemic-related issues (concern about the pandemic (very vs somewhat/not at all concerned); changes in physical activity and sleep (less vs more/same); difficulty obtaining food and medications and accessing routine care (any vs none)) were self-reported. Self-reported physical functioning and episodic and working memory performance were reported as t-scores (such that a score of 50=population mean and a 10-point difference=1 SD) and community mobility scores ranged from 0 to 120, with higher scores representing better functioning for all domains. Differences in scores were assessed via t-tests and age-adjusted, sex-adjusted and race-adjusted linear regression. Results: Among 245 participants (mean age, 46 years; 95% female, 77% black), physical functioning t-scores (mean=44) were consistently lower (by 3–5 points) for those who reported concern about the pandemic, less physical activity and sleep, difficulty obtaining food and medications, and accessing routine care. Similarly, community mobility scores (mean=48) were lower (by 10–20 points) for these individuals. There were no substantial differences in episodic memory and working memory t-scores (mean=50 and 47, respectively) by pandemic-related issues. Conclusion: We found that physical functioning and community mobility, but not cognition, were lower among those who reported more concern about the pandemic or greater disruptions to health routines. Future studies should explore interventions among these vulnerable individuals with SLE, who already disproportionately suffer from functional impairment, to maintain functioning and prevent adverse outcomes during times of crisis.